Early life circumstances and their impact on health in adulthood and later life: a systematic review - Weslley Barbosa Sales; Eunice Fernandes Maranhão; Caroline Sousa Truta Ramalho; Sabrina Gabrielle Gomes Fernandes Macêdo; Gérson Fonseca Souza; Álvaro Campos Cavalcanti Maciel (BMC Geriatrics)
Abstract Introduction Certain situations and contexts during early years of life and childhood can have a significant impact on the health of older individuals. Studies have demonstrated that adversities such as poverty, neglect, abuse, and exposure to chronic stress conditions during the early years of life are associated with a range of health problems in adulthood. Objective To systematically identify the literature on the impact of circumstances and/or conditions in early life/childhood on the health of older adults. Materials and methods A systematic literature review guided by the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) was conducted. The databases used were PUBMED, LILACS, Scielo, Embase, and Web of Science. Longitudinal studies published without language or publication date restrictions, related to the proposed theme, were included. Editorial letters, review protocols, reflective studies, literature reviews, and articles without available online abstracts or full texts were excluded. The quality assessment of the studies was conducted using tools and guidelines provided by the Joanna Briggs Institute. The database search conducted between May and August 2023 resulted in 8,224 articles found. After completing the steps of duplicate exclusion and reading titles and abstracts, 35 articles were selected for full reading, culminating in a final sample of 10 eligible articles for this review. Results These studies highlighted various early-life circumstances, including socioeconomic status, exposure to adverse childhood experiences, and environmental factors, demonstrating significant associations with health outcomes in older adults. The findings collectively emphasize the critical role that early adversities play in influencing chronic diseases, mental health, and overall well-being in later life. Final considerations Understanding social determinants, early-life adversities, and socioeconomic factors is essential for promoting healthy and equitable aging, with effective interventions and public policies aimed at reducing inequalities and ensuring the well-being of the adults and older adults.